Identification of DNA methylation based prognostic subtype and signature in epithelial ovarian cancer - Jingjing Zhou; Yuxin Chen; Wei Liu; Chao Wang; Lei Liu; Wei Geng; Linqing Chai; Dong Yang; Hongji Dai; Haixin Li; Yanrui Zhao; Kexin Chen; et al. (Human Genetics, 2026)

Necroptosis activates NLRP3 inflammasome to drive necroinflammation in T-2 toxin-induced cartilage damage - Meng Zhang; Jing Tian; Yinan Liu; Yawen Shi; Xiaoming Zhao; Xinhe Zhang; Xu Zhao; Lian Li; Chen Chen; Jinghong Chen (Food and Chemical Toxicology, 2026)

Embedding bio-Fenton in a hybrid membrane biofilm reactor enhances the treatment of antibiotic-contaminated saline water - Wei Li; Ying-Lian Lan; Xu Zhang; Yi-Hao Luo; Yu-Xiang Zhao; Ju-Ying Lei; Yong-Di Liu; Bruce E. Rittmann (Water Research, 2026)

A pair of newly isolated terpenylated coumarins from Notopterygium incisum roots with anti-inflammatory activity - Li-Lian Zhao; Fei-Yuan Deng; Li Huang; Wei-Jun Dong; Wei-Zhen Dong; Li-Jun Huang; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

An undescribed tirucallane-type triterpenoid with anti-inflammatory activity from Ailanthus altissima - Zhong-Fu Wang; Xiang Guo; Li Huang; Li-Lian Zhao; Jie Li; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2026)

A unified heterogeneous implementation of numerical atomic orbitals-based real-time TDDFT within the ABACUS package - Taoni Bao; Yuanbo Li; Zichao Deng; Haotian Zhao; Denghui Lu; Yike Huang; Chao Lian; Lixin He; Mohan Chen (Computer Physics Communications, 2026)

Involvement of sucrose transporter SUT4 in regulating tomato yield and fruit quality - Yufei Liang; Zhaoyuan Lian; Wenjing Dong; Shuyu Qi; Jingyi Zhao; Wanxing Hu; Ning Li; Haijun Gong (Plant Science, 2026)

Molten-salt assisted synthesis of MAX@straw composites for electromagnetic absorption - Zonglin Liu; Han Li; Xu Zhao; Fuhua Xue; He Chen; Qian Yan; Haowen Zheng; Huanxin Lian; Yunxiang Chen; Teng Fei; Baiqiao Bao; Qingyu Peng; et al. (Chemical Engineering Journal, 2026)

Mitochondria-targeted MET-MA carbon dots attenuate radiation-induced bone injury by preventing senescence via miMOMP - Jiajin Yang; Jiahe Zhao; Zhixuan Li; Zixi Tian; Yulu Wu; Haosen Lian; Honglin Li; Su Chen; Chunjie Li; Zhiyong Guo (Chemical Engineering Journal, 2026)

A decision-support framework for balancing growth, profit and environmental impacts in aquaculture feeding - Chunlin Chen; Youbang Guan; Lihua Song; Guoping Lian; Daoliang Li; Ran Zhao; Lian X. Liu; Michael Short (Aquacultural Engineering, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Reinforcing electrolyte skeleton via in-situ cross-link enhancement for solid-state lithium metal batteries - Ziwen Tian; Mohan Yang; Yutao Wang; Qiwei Wu; Yu Guan; Hao Men; Yali Li; Lian Wang; Yuefeng Su; Yong Zhao (Chemical Engineering Journal, 2026)

Screening of low-cost medium substitutes for pear tissue-cultured seedlings - Qiushi Liu; Chuqing Zhao; Lian Xue; Baihui Tian; Meiqing Pu; Feng Jiang; Tianzhong Li; Shengnan Wang (Plant Biotechnology Reports, 2026)

Epithelial-immune interface in asthma: Mechanistic insights driving novel therapeutic strategies - Jingyi Deng; Jun Zhao; Wenlu Zhu; Yuanhui Li; Dexin Nie; Yuyu Zhong; Xinlong Lian; Suidong Ouyang (Seminars in Immunopathology, 2026)

Two newly isolated compounds from Hansenia weberbaueriana and their anti-inflammatory potential - Jie Li; Su Hu; Li Huang; Li-Lian Zhao; Li-Jun Huang; Wei-Jun Dong; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Failure characteristics and development mechanism of time-delayed rockburst in a tunnel excavated via the drilling and blasting method: A case study - Lei Hu; Wen-Fei Chang; Ben-Guo He; Wei Zhang; Jun Zhao; Zhi-Bin Yao; Meng-Fei Jiang; Hong-Pu Li; Lian-Jie Fu (Tunnelling and Underground Space Technology, 2026)

Biochar-assisted copper removal and metabolic responses of Hydrocotyle vulgaris in a hydroponic system: Insights from untargeted metabolomics and computational modeling - Ziyi Lian; Xiaofan Fu; Haoran Yin; Yuxin Li; Lei Zhao; Jing Shang; Tian Gao; Bo Zhang; Chengbin Xu; Runjie Zhang; Fang Ma; Jieting Wu (Journal of Environmental Management, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Subtropical high-driven ozone pollution episodes in coastal cities in southeastern China - Lanbo Zhao; Lian Xue; Chengchun Shi; Chuanyou Ying; Erling Ni; Haoran Zhang; Xueyu Zhou; Tianshuai Li; Xin Huang; Aijun Ding (Atmospheric Environment, 2026)

Climate stability shaped fire regimes over the past ∼1400 years in northeastern China - Yufeng Yuan; Xin Zhou; Yong Luo; Anze Chen; Lize Meng; Changchun Huang; Lian Liu; Xiaoyan Liu; Hongfei Zhao; Shiwei Jiang; Xuanqiao Liu; Ming Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Combination of selenium and metformin mitigated testicular damage from diabetes mellitus by enhancing glycolysis via AMPK/ SIRT1 pathway - Li Cao; Zhihuan Chen; Haixin Li; Jie Zhao; Jianing Niu; Jing Ma; Xiaoqiang Lian (Journal of Trace Elements in Medicine and Biology, 2026)

A novel adaptive soil moisture retrieval method via stacked ensemble learning and a local Bayesian dynamic algorithm - Fuqiang Wang; Ruiping Li; Sinan Wang; Xiaoming Ma; Jinming Yang; Jialu Dai; Xiaohui Lian; Jianwei Zhao; Liying Zhou; Yanxin Wang (Journal of Hydrology, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Design of boron-based catalysts: Advances in promoting efficient propylene production via oxidative dehydrogenation of propane - Ying Liu; Jianjun Shi; Yang Dong; Yanrong Wang; Dongxu Han; Weiye Li; Dong Li; Lian Kong; Wenwen Ma; Zhen Zhao (Fuel, 2026)

Anisotropic stimuli-responsive hydrogel enabling tunable electromagnetic interference shielding and strain sensing - Qian Yan; Han Li; Teng Fei; Zonglin Liu; He Chen; Huanxin Lian; Yunxiang Chen; Haowen Zheng; Baiqiao Bao; Xu Zhao; Liangliang Xu; Fuhua Xue; et al. (Chemical Engineering Journal, 2026)

Androgen receptor–NOX4–necroptosis axis drives male-biased susceptibility in aristolochic acid-induced acute kidney injury - Haojie Wang; Yu Wang; Wenfei Lian; Minbo Yan; Junliang Qiu; Zheyi Zhao; Zhiwei Li; Yong Wang; Yashpal S. Kanwar; Yingbo Dai; Xiaoping Zheng (Chemico-Biological Interactions, 2026)

Coping with the concurrent PM2.5 and ozone pollution in Southwestern China under the impact of cross-border transport of biomass burning - Mingya Xie; Puyu Lian; Fei Qiu; Jian Wang; Feng Xiang; Yuheng Chen; Anjie Yin; Jiaqi Li; Kaihui Zhao (Atmospheric Research, 2026)

O, S, C isotopic signatures of high-arsenic groundwater in Ngari, Xizang: Seasonal-scale drivers of arsenic release mechanisms - Lian Song; Shehong Li; Jen-How Huang; Fei He; Qiao Han; Jie Liao; Zhenjie Zhao; Ci Ren Qu Ji; Yong Shui (Acta Geochimica, 2026)

Rock-Breaking Analysis and Structural Optimization of Convex-Ribbed Ridged Nonplanar PDC Cutters and Application - Lian Chen; Chuan Hu; Yingxin Yang; Xiaoqiang Peng; Zhengwei Li; Shiwei Niu; Jiayuan Zhao; Zhiqiang Fu (Rock Mechanics and Rock Engineering, 2026)

Sulfonylurea receptor integrates calcium homeostasis and insulin-like peptide signaling to regulate energy metabolism and larval development in Hyphantria cunea - Yue-Cheng Zhao; Rong-Man Gou; Haneef Tariq; Xi-Lin Li; Lian-Sheng Zang; Li-Wen Song (Insect Biochemistry and Molecular Biology, 2026)

Role of selenoprotein S downregulation in T-2 toxin-induced endoplasmic reticulum stress and myocardial injury - Yawen Shi; Kunpan Chen; Hui Wang; Meng Zhang; Yinan Liu; Xinhe Zhang; Lian Li; Xu Zhao; Yi Wang; Xuewei Yang; Xiaoming Zhao; Pinglin Yang; et al. (Chemico-Biological Interactions, 2026)

Rapid enrichment of ternary carbon-fixing microbial consortia from anaerobic sludge via pressurized pre-autotrophic strategy for scalable microbial electrosynthesis - Lin-xiao Li; Tian-tian Yang; Yue Yuan; Yi-lian Han; Qian Zhao; Wen-han Wang; Yue Sun; Xiao-xin Cao; Xin-lei Jiang; Tian Li; Xin Wang (Bioresource Technology, 2026)

Bifidobacterium animalis subsp. lactis GOLDGUT-BB69 Counteracts Diarrhea in Mice by Alleviating Inflammation, Enhancing Intestinal Barrier Functions, and Regulating Intestinal Microbiota - Meng Zhao; Chunjing Li; Zixun Fang; Qi Yi; Xuezhou Ke; Xia Luo; Lian Zhou; Qing Wang (Probiotics and Antimicrobial Proteins, 2026)

Vegetation restoration drives a shift from plant-derived to microbial-derived soil organic carbon accumulation in a semi-arid sandy land in China - Jiannan Lu; Yuqiang Li; Xuyang Wang; Chengzhuo Zheng; Jie Lian; Xueyong Zhao (Applied Soil Ecology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Bromate electroreduction on NiO/Ni foam: Overlooked role of ‘reef-sea’ synergetic catalytic mechanism - Tianqi Ji; Yue Cheng; Huihuan Lian; Junjie Li; Zhipeng Luo; Feiping Zhao; Ke Xiao; Huabin Zeng (Journal of Environmental Sciences, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

Controls on heavy metal variability in a coastal mountainous river: Impacts of tides, typhoons, and anthropogenic activities - Yalong Li; Ni Su; Yun Zhao; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Shouye Yang (Journal of Geochemical Exploration, 2026)

Sustainable construction of lignin-containing cellulose nanofibrils reinforced antifreeze deep eutectic solvent gel for wearable human motion strain sensors - Li-Li Sun; Jiao Zhao; Lian-Jie Zhao; Shao-Ni Sun; Xue-Fei Cao (Journal of Cleaner Production, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Daily Arctic first-year sea ice thickness observed by China’s GNSS-R satellite constellation - Yuan Li; Lei Zheng; Qi Liang; Teng Li; Chuyue Peng; Lian He; Qiuyang Zhao; Zhuoqi Chen; Qi Tang; Ying Li; Beibei Liang; Shengli Wu; et al. (Science Bulletin, 2026)

Evolution of particulate organic carbon fluxes in large river basins and their ecological driving mechanisms (1985–2021) - Maomao Li; Haikun Yang; Changsen Zhao; Yanqing Lian; Guoqing Wang (Journal of Hydrology, 2026)

Targeting the MLKL–F-actin–NLRP3 axis attenuates arsenic-induced myocardial necroinflammation - Yinan Liu; Yixin Cui; Meng Zhang; Yawen Shi; Xu Zhao; Xinhe Zhang; Lian Li; Pinglin Yang; Jinghong Chen (Food and Chemical Toxicology, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

An inverse effect of hydroxyl nest concentration on cobalt dispersion for propane dehydrogenation - Yiyi Wang; Yijing Xia; Dong Li; Yangyang Song; Zean Xie; Yu Ren; Wencui Li; Xiaoqiang Fan; Lian Kong; Xia Xiao; Peng Tian; Zhen Zhao (Chemical Engineering Journal, 2026)

Robust, reusable, and closed-loop recyclable epoxy adhesives via parallel dual-dynamic covalent crosslinking network design - Xuebin Lian; Dehuan Kong; Yuanjian Li; Shujun Zhao (Chemical Engineering Journal, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

13-cis-retinoic acid modulates porcine ovarian granulosa cell differentiation via retinoic acid signaling-FoxA1 axis: Implications for ovarian follicular development and luteinization - Hong-Liang Zhang; Hua-Biao Wang; Yi-Xuan Mi; Xia-Meng Wu; Li Bao; Ming Zhao; Li Ma; Shui-Lian Wang (Theriogenology, 2026)

Identification and expression analysis of glutamate receptor-like (GLR) genes and cold response of VaGLR3.4 in grapevine - Ziyang Qu; Jinhua Li; Shuqi Lian; Ting Zhao; Ling Wang; Chaohong Zhang (Physiology and Molecular Biology of Plants, 2026)

Vertical bearing behavior and influence depth of the five-bucket foundation for offshore wind turbines in layered soil conditions - Jijian Lian; Yaqian Zhao; Jiale Li; Yaohua Guo; Haijun Wang (Ocean Engineering, 2025)

Heterogeneous electro-Fenton like process by iron-doped nickel phosphide catalyst for dibutyl phthalate degradation within a wide pH range - Ruo He; Rui Zhou; Hang Xu; Li-Kun Xu; Chen-Yi Xu; Lian-Feng Mei; Wen-Zhao Zhou; Hong-Yu Meng; Xin Zhang (Journal of Environmental Chemical Engineering, 2025)

Effects of roasting on the quality characteristics, sensory profiles, and volatile flavor compounds of different cuts of Yanbian yellow beef - Bowen Qin; Xiangji Meng; Rufeng Lian; Jinlong Tan; Chunxiang Piao; Juan Wang; Hongmei Li; Changcheng Zhao; Baide Mu; Guanhao Li (International Journal of Gastronomy and Food Science, 2025)

Integrative transcriptomics and QTL analysis identify lactoperoxidase and deubiquitinase as key targets for mastitis control in dairy animals - Jie Su; Fei Wang; Runshi Li; Lin Guo; Xianghai Ma; Xiaoyan Wang; Junyu Zhang; Shuaitao Lian; Jiaoxiong Xue; Jianglin Zhao; Yong Zhang; Xu Liu; et al. (Food Bioscience, 2025)

Soil extracellular enzyme stoichiometry reveals the nutrient limitations of soil microbial metabolism under precipitation changes in Ningxia desert steppe of China - Jiali Lian; Jing Chen; Cui Han; Ying Zhao; Xueqin Yang; Jianping Li (European Journal of Soil Biology, 2025)

Synbiotic Effects of Lacticaseibacillus paracasei K56 and Prebiotics on the Intestinal Microecology of Children with Obesity - Pengwei Zhang; Xianhui Dong; Yijun Zeng; Junkui Chen; Sijia Yang; Peipei Yu; Chunhong Ye; Wei-Lian Hung; Qiuyue Jiang; Wen Zhao; Zhaozhong Zeng; Jinjun Li; et al. (Probiotics and Antimicrobial Proteins, 2025)

Serum amyloid A: multifaceted roles in inflammation and cellular interactions - Shouzheng Cheng; Dingyu Duan; Hao Cui; Yingying Lian; Fan Jiang; Qianming Chen; Taiwen Li; Lei Zhao (Immunologic Research, 2025)

Genome-wide identification of TCP gene family and gene editing of BjTCP18 genes increases branching in Brassica juncea - Shuangping Heng; Meng Li; Rouyi Zhao; Boning Cao; Wei Zeng; Guangzhi Mao; Feng Xing; Shuaibin Lian; Shaoheng Zhang (Functional & Integrative Genomics, 2025)

Building regulatory resilience in shipping: green technology licensing and carbon tax policies - Ying Shi; Jin Li; Xiaozhi Feng; Zhaotong Lian; Min Zhao (Frontiers in Marine Science, 2025)
As global concerns over carbon emissions intensify, regulators worldwide have implemented diverse carbon tax policies, each shaped by specific environmental objectives and economic considerations. In response, shipping carriers have increasingly invested in Research and Development (R&D) or purchased low-carbon technologies to comply with varying regulatory standards and maintain market competitiveness. Against this backdrop, this study develops game-theoretic models to analyze optimal technology licensing strategies for shipping carriers holding carbon-reduction technology in a competitive market. It further examines how regulators can set appropriate carbon tax levels to influence licensing behaviors under different policy objectives. Our findings reveal that when the implementation costs of the green technology are manageable, sole licensing can effectively align regulatory goals with carriers’ profit objectives. However, as costs increase, the patentee carrier may gradually prefer licensing strategies that restrict the technology adoption to only the carrier with lower initial carbon efficiency, deviating from the regulator's intended outcome. If the regulator's goal is to maximize the adoption of green technology, it can realign incentives or achieve suboptimal outcomes by lowering carbon taxes or offering subsidies. Conversely, if the regulator is more focused on social welfare, the most robust choice is to set the tax at a level that maximizes welfare under sole licensing conditions. Finally, we find that providing carbon tax discounts to carriers implementing green technology does not alter the decision structure but can amplify the advantages of sole licensing, resulting in higher social welfare.

Population Pharmacokinetics of Intravenous Levetiracetam in Neurosurgical Patients: Dosage Optimization Based on CrCl and Mannitol Use - Jinwei Fan; Jinhui Xu; Xianglong Chen; Peng Deng; Chunmeng Xue; Shenjia Huang; Hanzhen Zhao; Tongtong Li; Lijuan Yang; Yanxia Yu; Jinhong Qian; Mian Ma; et al. (Pharmaceutical Research, 2025)

Identification and Genomic Analysis of a New Viral Species With Low Similarity to Existing Viruses - Zhaobin Zheng; Lei Zhao; Yundan Liu; Wei Wang; Kaiyang Zheng; Xin Chen; Suqing Zhang; Yue Sun; Zhe Ma; Hongbing Shao; Yeong Yik Sung; Wen Jye Mok; et al. (Environmental Microbiology, 2025)
Viruses are among the most abundant and diverse biological entities on Earth. Over the past decades, metagenomic sequencing has revealed thousands of viral genomes. However, viral isolation methods remain indispensable for discovering viruses that are missed by metagenomic sequencing due to limitations like low abundance (1, 2). Here, a novel phage, vB_PshM_Y4, which infects Pseudoalteromonas shioyasakiensis , an economically important, opportunistic marine pathogen was isolated. A comparison of vB_PshM_Y4 with over 15 million viral genomes, including both cultivated and uncultivated viruses in the NCBI and IMG/VR v4 datasets, found no closely related genome. This study provides evidence that traditional isolation methods can detect viruses that cannot be identified through metagenomic sequencing. In addition, a comparison of virus isolates deposited in the NCBI database with uncultured viruses in the IMG/VR viral database shows that approximately only half of the isolates can be detected using metagenomic approaches. Notably, viruses that are not able to be detected by metagenomic sequencing often exhibit low abundance and possess unique genomes. These results suggest that traditional viral isolation methods remain important for obtaining rare, low‐abundance viruses and underscore the significance of traditional experimental methods in the era of metagenomes.

A pair of lignans isolated from Trachelospermum jasminoides and their anti-inflammatory activity - Chen-Yi Yan; Miao Wang; Yu-Ting Mu; Li-Lian Zhao; Yu-Liang Guo; Wei-Zhen Dong; Yun Deng; Da-Le Guo (Phytochemistry Letters, 2025)

Challenges of precise aeration implementation in conventional wastewater treatment processes: A review - Hongyi Li; Jian Xu; Yingxin Zhao; Jijian Lian (Journal of Water Process Engineering, 2025)

Light-driven deep desulfurization: Efficient photo-thermal catalysis with PW9-NH2-UiO-66(Zr/Ce)/g-C3N4 heterostructures - Kexin Liang; Wenwen Ma; Linjiao Yang; Dong Li; Hua Yao; Danyi Zhang; Xu Yang; Lian Kong; Zhen Zhao (Journal of Environmental Chemical Engineering, 2025)

Regulation mechanism and resistant strain based bioaugmentation of anammox consortia in response to triclocarban - Jia-Hui Yang; Wei-Lin Guo; Zhe-Qi Lian; Qi Su; Xin-Yi Zhao; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Chemical Engineering Journal, 2025)

Exploring utilization of tourmaline in constructed wetlands to enhance nutrient reduction under fluoride stress: Performance and microbial mechanism - Lingyan Zhao; Jian Zhang; Mingjun Li; Peihao Yan; Jianjun Lian; Zizhang Guo; Haiming Wu (Chemical Engineering Journal, 2025)

Selectively passivated core-satellite cobalt-iron bimetallic phosphide with optimized ⁎OH adsorption for boosting oxygen evolution reaction - Baoshan Liu; Wangshu Zheng; Zhaoxi Zhang; Jiarui Yang; Yanqi Yuan; Feng Li; Jing Liu; Liping Zhao; Ming Wen; Han Chen; Peng Zhang; Lian Gao (Chemical Engineering Journal, 2025)

Tailoring spatial distribution of hydroxyl groups in metal-organic framework for enhanced lead ion adsorption - Xinli Gao; Xiule Lian; Puyang Chen; Sufang Song; Zhengjie Li; Xudong Zhao (Chemical Engineering Journal, 2025)

Microbial diversity outweighs plant diversity in mediating the response of ecosystem multifunctionality to altered precipitation in a desert steppe - Cui Han; Yi Zhang; Xu Luo; Ying Zhao; Xueqin Yang; Jiali Lian; Jianping Li (Plant and Soil, 2025)

Therapeutic effects of Scutellaria baicalensis total flavonoids on metabolic syndrome in rats via modulation of PPARα and PPARγ signaling - Yang Zhou; Zhi-Ping Li; Yu-Hang Lian; Xin Gao; Song-He Yin; Yu-Mei Zhao (Journal of Molecular Histology, 2025)

Hypersonic trajectory prediction based on partially observable information - Fangjia Lian; Bangjie Li; Qisong Yang; Jiufen Zhao (Advances in Space Research, 2025)

An overview of extreme weather-epidemic compound disasters - Jianping Huang; Xinbo Lian; Huijun Wang; Tong Zhu; Han Li; Yingjie Zhao; Rui Wang; Danfeng Wang; Wei Yan; Shujuan Hu; Xiaodan Guan; Shanshan Wang (Science Bulletin, 2025)

Magnetic coconut shell biochar driven leachate activated sludge system treatment efficiency, antibiotic resistance gene response, and microbial community succession - Qiaona Xie; Kangbo Zhao; Yiting Lian; Siyi Li; Hongyuan Liu; Yuyang Long; Chengran Fang (Journal of Environmental Management, 2025)

Correction to: Overexpression of Tau Rescues Nogo-66-Induced Neurite Outgrowth Inhibition In Vitro - Yu-Chao Zuo; Hong-Lian Li; Nan-Xiang Xiong; Jian-Ying Shen; Yi-Zhi Huang; Peng Fu; Hong-Yang Zhao (Neuroscience Bulletin, 2025)

MLKL triggers NLRP3 activation in sodium arsenite-induced myocardial necroinflammation - Yixin Cui; Meng Zhang; Yi Xiao; Jinren Liu; Yonghui Chen; Xingran Ruan; Xu Zhao; Yinan Liu; Yawen Shi; Jing Tian; Lian Li; Xinhe Zhang; et al. (Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dissipation of penthiopyrad in polyethylene microplastics coexisting soils: Roles of soil properties and microbial communities - Miqi Li; Hui Liu; Kexin Zhang; Chengjie Lian; Xintong Wang; Danyang Zhao; Yunqi Cao (Pesticide Biochemistry and Physiology, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Impact of ectomycorrhizal symbiosis on root system architecture and nutrient absorption in Chinese chestnut and pecan seedlings - Ting Chen; Cancan Zhu; Shucheng Li; Yan Xia; Jian Huang; Wu Wang; Chunlan Lian; Yu Chen; Yuqiang Zhao; Shijie Zhang (Plant and Soil, 2025)

Optimizing the support morphology to boost ultra-deep hydrodesulfurization of diesel over NiMo/Al2O3 catalysts - Yitong Sun; Wenwen Ma; Ke Yu; Dong Li; Weiming Kong; Lian Kong; Zhen Zhao (Fuel, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Whole grain black rice: a paradigm shift from mainly calories to a nutritious food that benefits human health - Zenan Yang; Dianwei Li; Ruixue Wei; Xiaochi Zhao; Xingming Lian; Chao Ren; Jinghua Xiao; Yanhua Li; Xuan Chen; Rod A. Wing; Qifa Zhang; Hao Chen (Science China Life Sciences, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

Degradation of typical tetracycline antibiotics in landfill leachate by three-dimensional aerated electrocatalytic reactor (3D-AER): electrode properties, influencing factors and degradation mechanism - Qiaona Xie; Kangbo Zhao; Siyi Li; Yiting Lian; Mingdi Yang; Hongyuan Liu; Chuanlong Chen; Chengran Fang (Journal of Environmental Management, 2025)

Assessing effect of toluene on immobilized denitrifying microorganisms: Enzyme activity, electronic behavior, and microbial community - Kun Wu; Chenxi Li; Nengsheng Liu; Liuzhou Chen; Yingjie Lian; Quanlin Zhao; Zhengfang Ye (Journal of Environmental Chemical Engineering, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Deep Learning-Based Surrogate-Assisted Intelligent Optimization Framework for Reservoir Production Schemes - Lian Wang; Hehua Wang; Liehui Zhang; Liang Zhang; Rui Deng; Bing Xu; Xing Zhao; Chunxiang Zhou; Li Fan; Xindong Lv; Junda Wu (Natural Resources Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Optimized immobilization of lead and cadmium in soil using dithiocarboxy functionalized silica: A long-term effectiveness study - Mingming Lian; Chaoran Li; Longfei Wang; Liyong Niu; Linlin Zhao; Dongdong Wu; Zongsheng Zhao; Xiaohong Li; Zhijun Zhang (Journal of Hazardous Materials, 2025)

Attention scores and peak perception in long-term ozone prediction using deep learning - Zhihao Xu; Danni Xu; Wenguang Li; Puyu Lian; Yuheng Chen; Fangyuan Yang; Kaihui Zhao (Environmental Modelling & Software, 2025)

Analysis of occupant thermal comfort and energy-saving potential based on cooling behaviors in residential buildings: A case study of Shanghai - Junmeng Lyu; Yuxin Yang; Dayi Lai; Li Lan; Zisheng Zhao; Heng Du; Zhiwei Lian (Building and Environment, 2025)

Research on the analysis of morphological characteristics in pediatric femoral neck fractures utilizing 3D CT mapping - Niu-Niu Zhao; Xue-Lian Gu; Zhen-Zhen Dai; Chen-Chen Wu; Tian-Yi Zhang; Hai Li (Medical & Biological Engineering & Computing, 2025)

Rural depopulation has reshaped the plant diversity distribution pattern in China - Qing Luo; Cuiwei Zhao; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; Yingying Xue; Mingkang Long; et al. (Resources, Conservation and Recycling, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Full-scale shaking table test on a precast sandwich wall panel structure with a high-damping viscoelastic isolation and mitigation device - Zhong-Wei Hu; Zhao-Dong Xu; Lian-Yu Zhang; Jia-Xuan He; Zheng-Han Chen; Qi-Song Miao; Wen-Feng Li (Engineering Structures, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Stress-induced self-assembly of hierarchically twisted stripe arrays - Zhenghao Zhang; Zekai Zhang; Junyu Hou; Yiyue Zhao; Jia Jia; Jiwei Wang; Jie Zhao; Cheng Lian; Angang Dong; Dongyuan Zhao; Wei Li (Science Bulletin, 2025)

Mechanism of anti-hepatitis potential of Tagetes erecta L.: UPLC-Q-TOF-M S/MS, network pharmacology, molecular docking and in vitro experimental validation - Jiangning Peng; Zhenxia Zhao; Zhiqian Yuan; Yingfeng Du; Hong Wang; Yunhe Lian; Xinyi Yang; Hui Li (Next Research, 2025)

Exploring the anti-inflammatory potential of Lacticaseibacillus paracasei postbiotics: Mechanistic insights and functional components - Yuhang Sun; Zhe Sun; Bing Fang; Ran Wang; Yue Liu; Jingyu Li; Hanglian Lan; Wen Zhao; Wei-Lian Hung; Ming Zhang (Food Bioscience, 2025)

Study on the posture control strategy of sinking and penetration characteristics of hexagonal thick-walled multi-compartment bucket foundation - Xinyi Li; Jijian Lian; Zhaolin Jia; Nan Shao; Yaohua Guo; Haijun Wang; Hao Zhao; Zhichuan Wu; Guanhao Zhang; Weipeng Feng (Ocean Engineering, 2025)

Precipitation addition during growing and non-growing seasons interactively affects the abundance of soil nematode communities in a semi-arid steppe - Yaning Li; Jingwei Guo; Xun Wang; Taohui Lian; Rong Yuan; Jiarui Feng; Cancan Zhao; Renhui Miao; Yinzhan Liu (CATENA, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Study on the condensate gas phase behavior in Nano-porous media - Ping Wang; Yuepeng Jia; Junjie Zhong; Wensong Huang; Wei Ding; Peng Lian; Xiangwen Kong; Li Liu; Zibin Zhao (Fuel, 2025)

NiO enhancing CoOx reducibility against deactivation of propane dehydrogenation reaction caused by trace oxygen in industrial propane feedstock - Zean Xie; Yan Wang; Yangyang Song; Dong Li; Xiaoqiang Fan; Lian Kong; Xia Xiao; Zhen Zhao (Chemical Engineering Journal, 2025)

Manipulating weak interactions between host/guest and analytes in Cu(I)-cluster-based MOF for fluorescent gas sensing towards chlorinated volatile organic compounds - Yunfang Zhao; Yangxingyu Ye; Zhiyuan Wu; Jiaxin Jiang; Zhijia Li; Hang Lei; Feilong Jiang; Lian Chen; Maochun Hong (Chemical Engineering Journal, 2025)

Hierarchical carbon-incorporated boron nitride derived from protein flocculation for efficient oxidative dehydrogenation of propane - Dong Li; Yanjun Chen; Mengyao Sun; Wenwen Ma; Zean Xie; Lian Kong; Shuchong Bai; Zhen Zhao (Chemical Engineering Journal, 2025)

Significantly improving the stability of high-entropy PtFeNiCoMn nanoalloys by nitrogen doping in oxygen electrocatalysis - Mang Niu; Qinhe Guan; Weiyong Yuan; Chun Xian Guo; Dapeng Cao; Chang Ming Li; Lian Ying Zhang; Xiu Song Zhao (Chemical Engineering Journal, 2025)

Mitochondrial Uncoupling Protein-2 Ameliorates Ischemic Stroke by Inhibiting Ferroptosis-Induced Brain Injury and Neuroinflammation - Lei Wang; Xiaona Li; Lili Chen; Shenglan Mei; Qianni Shen; Lian Liu; Xuke Liu; Shichong Liao; Bo Zhao; Yannan Chen; Jiabao Hou (Molecular Neurobiology, 2025)

Similar tolerance of urban birds towards both benign human and lethal cat predators - Hong-Yan Ye; Jing Yu; Kang Hong; Ya-Lian Li; Jin-Ming Zhao (Journal of Ornithology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Numerical study on wave propagating characteristics through an offshore pile-net enclosure structure - Yun-Peng Zhao; Lian-Xin Xin; Chao Ma; Ke-Zhao Fang; Yi-Xin Li; Chun-Wei Bi (Ocean Engineering, 2024)

Accumulation modes and effects of differentially charged polystyrene nano/microplastics in water spinach (Ipomoea aquatica F.) - Yachuan Zhao; Ao Du; Tida Ge; Gang Li; Xiaoqing Lian; Shufeng Zhang; Can Hu; Xufeng Wang (Journal of Hazardous Materials, 2024)

The restoration of karst rocky desertification has enhanced the carbon sequestration capacity of the ecosystem in southern China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Jinfeng Wang; Luhua Wu; Chaojun Li; Junhan Li; Yuanhuan Xie; Chen Ran; et al. (Global and Planetary Change, 2024)

Vine tea kombucha ameliorates non-alcoholic fatty liver disease in high-fat diet fed mice via antioxidation, anti-inflammation and regulation of gut microbiota - Jin Cheng; Si-Yu Huang; Ruo-Gu Xiong; Si-Xia Wu; Zhi-Jun Yang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Hui-Lian Zhu; Hua-Bin Li (Food Bioscience, 2024)

Boosting seawater denitrification in an electrochemical flow cell - Ding Li; Shuang-Cheng Jiang; Jia-Fang Xie; Jian Zhang; Ying-Lian Zheng; Quan-Bao Zhao; Han-Qing Yu (Water Research, 2024)

Froth flotation separation of fluorite ore using(E)-N-(2-hydroxyethyl)octadec-9-enamide as the flotation collector - Yuxuan Liu; Jianli Tian; Zeyong Lu; Ke Xue; Yabing Miao; Wenpo Zhao; Jiaxiang Zhu; Yisheng Wang; Lian Wang; Wenfeng Li (Minerals Engineering, 2024)

Mechanically and accurately calculate river width in vegetation areas by coupling Sentinel-1 and -2 imageries within land-water-mixed pixels - Maomao Li; Changsen Zhao; Zhen Duan; Hongguang Cheng; Yanqing Lian; Guoqing Wang (Journal of Hydrology, 2024)

Enhancing the resistance of single-atom and cluster catalysts in CO-SCR to water, sulfur, and oxygen via structural engineering - Huanli Wang; Dianxing Lian; Mohaoyang Chen; Chenxi Li; Guiyao Dai; Shujun Hou; Botao Liu; Ke Wu; Guofeng Zhao; Weiwei Zhang; Yuxi Liu; Yongjun Ji (Chemical Engineering Journal, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Unexpected response of terrestrial carbon sink to rural depopulation in China - Qing Luo; Xiaoyong Bai; Cuiwei Zhao; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; Yingying Xue; et al. (Science of The Total Environment, 2024)

Sensitive colorimetric detection of Vibrio vulnificus based on target-induced shielding against the peroxidase-mimicking activity of CeO2@PtRu nanozyme - Chenjing Xu; Jinpo Xie; Lian Yu; Bin Shu; Xiaogang Liu; Siping Chen; Qinglan Li; Shaohai Qi; Suqing Zhao (Food Chemistry, 2024)

In-situ assembly of polypyrrole onto heterocyclic aramid for high-strength, ultratough, durable, and multifunctional films - Jinhua Xiong; Xu Zhao; Pengyang Li; Huanxin Lian; Qian Yan; He Chen; Zonglin Liu; Zhong Chen; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2024)

WOx-Carbon nanorods catalyzed photoelectrochemical hydrogen evolution reaction of silicon-photocathode in acidic media - Baoshan Liu; Jiarui Yang; Feng Li; Jing Liu; Liping Zhao; Lijie Sun; Han Chen; Peng Zhang; Lian Gao (Chemical Engineering Journal, 2024)

Hybrid molecularly imprinted polymers for targeted separation and enrichment of 10-hydroxycamptothecin in Camptotheca acuminata Decne - Yanwei Xu; Yulian Tan; Zahid Majeed; Fang Nie; Kaili Zheng; Zhonghao Li; Lian Yang; Chunjian Zhao; Chunying Li (Natural Product Research, 2024)

Low expression of selenoprotein S induces oxidative damage in cartilages - Yixin Cui; Yucheng Liao; Yonghui Chen; Xu Zhao; Yi Zhang; Hui Wang; Lian Li; Xinhe Zhang; Kunpan Chen; Mingzhao Jia; Jing Tian; Xingran Ruan; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Global response of soil biodiversity to climate and land use changes - Xiaoqian Shen; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Guangjie Luo; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Zilin Li; et al. (Journal of Cleaner Production, 2024)

Measurement of 224Ra in water via pulsed ionization chamber (PIC) radon detector - Haowei Xu; Chunqian Li; Pengxia Liu; Wen Liu; Shibin Zhao; Natasha T. Dimova; Xiliang Cui; Lijun Song; Tianyi Zhu; Ergang Lian; Chun Xia; Yanming Xue; et al. (Journal of Environmental Radioactivity, 2024)

The photosynthetic toxicity of nano-polystyrene to Microcystis aeruginosa is influenced by surface modification and light intensity - Kui Xu; Libin Zhao; Philippe Juneau; Zhen Chen; Xiafei Zheng; Yingli Lian; Weizhi Li; Peihuan Huang; Qingyun Yan; Xiongwen Chen; Zhili He (Environmental Pollution, 2024)

N-th root slant stack for enhancing weak seismic signals - Fei Li; Jun-fa Xie; Zong-hui Yao; Mei Li; Yu-lian Zhao; Wei-ming Liu; Juan Chen (Applied Geophysics, 2024)

Investigating well water level oscillations caused by seismic waves using automatically detected responses - Menghan Cao; Lian Xue; Li Zhao (Journal of Hydrology, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Impact of stratospheric intrusions on surface ozone enhancement in Hong Kong in the lower troposphere: Implications for ozone control strategy - Kaihui Zhao; Yuheng Chen; Puyu Lian; Wenguang Li; Fangyuan Yang; Xiufang Zhang; Ruowen Yang (Atmospheric Environment, 2024)

Aptamer based hybrid monolithic pipette tips supported by melamine sponge for enrichment of proteins - Yue-lun Sun; Jie Cheng; Bin-bin Liu; Jun-qin qiao; Ling-yu Zhao; Hong-zhen Lian; Li Mao (Analytica Chimica Acta, 2024)

Regeneration of sedimentary manganese in coastal sediments deciphered by 224Ra/228Th disequilibria - Zhongliang Lin; Li Liu; Ergang Lian; Weiqiang Zhao; Xinyu Jiang (Science of The Total Environment, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

Short-time potentiostatic assisted borate to induce the generation of ultrathin NiFe LDH active phase for industrial-level water oxidation - Yu Ma; Jia-Jun Wang; Xiao-Han Liu; Na Xu; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Anthropogenic activities alter the hydrological process of submarine groundwater discharge in a coastal area of Shanghai City, China - Dongsheng Li; Zhongfang Liu; Yunduo Zhao; Ergang Lian; Yue Zhang; Zijun Wu (Journal of Hydrology, 2024)

Plant growth-promoting bacteria improve the Cd phytoremediation efficiency of soils contaminated with PE–Cd complex pollution by influencing the rhizosphere microbiome of sorghum - Yong-Qi Liu; Yan Chen; Yu-Ying Li; Chuan-Yu Ding; Bai-Lian Li; Hui Han; Zhao-Jin Chen (Journal of Hazardous Materials, 2024)

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

A multi-functional CoN-Mo2N heterostructure nanorods for high performance lithium-sulfur batteries - Chun Xu; Xiangli Jiang; Minggang Huang; Wei Luo; Shan Zhang; Shuo Zhao; Guochun Li; Jiabiao Lian (Chemical Engineering Journal, 2024)

The genesis of the Tianbaoshan PbZn deposit in Sichuan, SW China: Insights from sphalerite and fluid inclusion compositions - Lian-Qing Zhao; Pei Ni; Wen-Sheng Li; Stefano Albanese; Kai-Han Zhang; Guo-Guang Wang; Jun-Yi Pan (Journal of Geochemical Exploration, 2024)

Construction of Co-ZIF-derived CoS2@Cu hollow heterogeneous nanotube array for the detection of hydrazine in environmental water samples - Lian Ou; Jie Yang; Li Xu; Shan Zhao; Xiaoli Xiong; Ting Xiao (Environmental Research, 2024)

Genomic and transcriptomic analyses provide new insights into the allelochemical degradation preference of a novel Acinetobacter strain - Lian Xu; Yang Zhao; Yue Li; Ji-Quan Sun (Environmental Research, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Bbhox2 is a key regulator for conidiation and virulence in Beauveria bassiana - Juanjuan Li; Yan Zhang; Shouhao Jiao; Lian He; Yanhua Fan; Xuemeng Han; Binda Sun; Wenqi Zhao; Yanlin Mei; Ning Wei; Haiyue Zeng; Dan Jin (Journal of Invertebrate Pathology, 2024)

Designing and preparing supramolecular encapsulation systems based on fraxetin and cyclodextrins for highly selective detection of nicotine - Yun-Han Yang; Zhen Zhang; Qiu-Lian Bao; Fang Zhao; Ming-Kun Yang; Xin Tao; Yan Chen; Jun-Tong Zhang; Li-Juan Yang (Carbohydrate Polymers, 2024)

Storage, form, and influencing factors of karst inorganic carbon in a carbonate area in China - Chaochao Du; Xiaoyong Bai; Yangbing Li; Qiu Tan; Cuiwei Zhao; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; et al. (Science China Earth Sciences, 2024)

Angelica dahurica extract and its effective component bergapten alleviated hepatic fibrosis by activating FXR signaling pathway - Chong Gao; Zhong-He Hu; Zhen-Yu Cui; Yu-Chen Jiang; Jia-Yi Dou; Zhao-Xu Li; Li-Hua Lian; Ji-Xing Nan; Yan-Ling Wu (Journal of Natural Medicines, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

Reinitiation of modern-style plate tectonics in the Early Neoproterozoic: Evidence from a ∼930 Ma blueschist-facies terrane in South China - Li-Guang Wu; Yi Chen; Richard M. Palin; Qiu-Li Li; Lei Zhao; Yi-Bing Li; Chao-Feng Li; You-Lian Li; Xian-Hua Li (Precambrian Research, 2024)

A DM9-containing protein from crab Eriocheir sinensis functions as a novel multipotent pattern recognition receptor - Yinan Li; Wenwen Yang; Jiejie Sun; Xingye Lian; Xiaopeng Li; Xinyu Zhao; Yu Liu; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2024)

High-efficiency solar-driven water purification enhanced by the in-plane temperature gradient and hydrated ions - Renjie Ding; Jinhua Xiong; Qian Yan; Pengyang Li; Xu Zhao; Zhong Chen; Zonglin Liu; Huanxin Lian; Zhigong Tang; Shanyi Du; Qingyu Peng; Xiaodong He (Chemical Engineering Journal, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Dryness stress weakens the sustainability of global vegetation cooling - Zilin Li; Xiaoyong Bai; Qiu Tan; Cuiwei Zhao; Yangbing Li; Guangjie Luo; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Lian Xiong; Fengjiao Song; et al. (Science of The Total Environment, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Spatial and Temporal Exhumation of the Northeastern China: Insights From Low Temperature Thermochronology - Yannan Wang; Lian Chen; Jin Zhang; Cunliang Zhao; Heng Zhao; Wenmu Guo; Junfeng Qu; Yingjie Li (Island Arc, 2024)
The northeastern (NE) China has undergone a long‐term tectonic history involving subduction–accretion of the Siberian Craton, North China Craton, and Western Pacific Plate, providing an ideal target for understanding the interactions between cratons and the Pacific oceanic lithosphere. However, the Mesozoic‐Cenozoic geological and topographic evolutions of the NE China remain unclear. Here, we present new apatite fission track data from Precambrian metamorphic rocks in the Lesser Hinggan Mountains. Apatite fission track dating yielded a group of central ages ranging from 130 ± 18 to 151 ± 11 Ma with mean track lengths varying between 13.67 ± 0.13 and 14.49 ± 0.08 μm. Thermal modeling results revealed a rapid cooling event at ca. 165–140 Ma, which was related to compressional deformations driven by shallow subduction of the Paleo‐Pacific Ocean Plate beneath the northeastern China. Furthermore, regional low temperature thermochronological datasets in NE China show additional three rapid exhumation stages, including the Early Jurassic (ca. 200–180 Ma), Early Cretaceous (ca. 120–100 Ma), and Late Cretaceous (ca. 80–60 Ma). They were associated with closure of the Mudanjiang Ocean, slab rollback of the Paleo‐Pacific Plate, and collision between the Okhotomorsk Block and southeastern Asia. As the Cenozoic, slow exhumation has emerged throughout the northeastern China.

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Three closely-related subclasses Phacodiniidia Small & Lynn, 1985, Protohypotrichia Shi et al., 1999, and Euplotia Jankowski, 1979 (Protista, Ciliophora): A new contribution to their phylogeny with reconsiderations on the evolutionary hypotheses - Chunyu Lian; Yan Zhao; Ping Li; Tengteng Zhang; Khaled A.S. Al-Rasheid; Naomi A. Stover; Yurui Wang; Chen Shao (Molecular Phylogenetics and Evolution, 2023)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

FUL homologous gene CmFL1 is involved in regulating flowering time and floret numbers in Chrysanthemum morifolium - Kunkun Zhao; Diwen Jia; Xue Zhang; Song Li; Jiangshuo Su; Jiafu Jiang; Sumei Chen; Fadi Chen; Lian Ding (Plant Science, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

The MKK3–MPK7 cascade phosphorylates ERF4 and promotes its rapid degradation to release seed dormancy in Arabidopsis - Xi Chen; Qiujia Li; Ling Ding; Shengnan Zhang; Siyao Shan; Xiong Xiong; Wenhui Jiang; Bo Zhao; Liying Zhang; Ying Luo; Yiming Lian; Xiuqin Kong; et al. (Molecular Plant, 2023)

Spring photosynthetic phenology of Chinese vegetation in response to climate change and its impact on net primary productivity - Yingying Xue; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Sirui Zhang; Min Liu; et al. (Agricultural and Forest Meteorology, 2023)

Attenuation effects of ZVI/PDS pretreatment on propagation of antibiotic resistance genes in bioreactors: Driven by antibiotic residues and sulfate assimilation - Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Qi-Shi Si; Lu-Shi Sun; De-Nian Li; Nan-Qi Ren; Wan-Qian Guo (Journal of Hazardous Materials, 2023)

Effect of biochar-derived dissolved organic matter on tetracycline sorption by KMnO4-modified biochar - Kaiyue Yin; Juyuan Wang; Xiaofei Tian; Na Yu; Xuexue Zhang; Yingying Zhao; Yuehua Liu; Shunchang Sui; Cuiping Wang; Fei Lian; Sheng Zhai; Xiaoyun Li; et al. (Chemical Engineering Journal, 2023)

Size-dependent chemical composition of atmospheric nanoparticles in urban Beijing during springtime - Yan Chen; Chenjuan Deng; Ting Lei; Junling Li; Chaofan Lian; Yiran Li; Jun Zheng; Jun Zhao; Dongbin Wang; Zhijun Wu; Lin Wang; Lei Li; et al. (Atmospheric Environment, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Biogeographic diversification of Actaea (Ranunculaceae): Insights into the historical assembly of deciduous broad-leaved forests in the Northern Hemisphere - Yuan-Yuan Ling; Kun-Li Xiang; Huan-Wen Peng; Andrey S. Erst; Lian Lian; Liang Zhao; Florian Jabbour; Wei Wang (Molecular Phylogenetics and Evolution, 2023)

Gender differences in thermal comfort under coupled environmental factors - Heng Du; Zisheng Zhao; Junmeng Lyu; Jinbo Li; Zhiqiang liu; Xiangyang Li; Yuxin Yang; Li Lan; Zhiwei Lian (Energy and Buildings, 2023)

An advanced CoNb2O6 anode material with in-situ interstitial doping for high-rate lithium-ion batteries - Shuo Zhao; Ting Chen; Hongping Li; Yuanfeng Liu; Minggang Huang; Chun Xu; Yingxue Cui; Guochun Li; Jiabiao Lian; Yong Wang (Chemical Engineering Journal, 2023)

Featured immune characteristics of COVID-19 and systemic lupus erythematosus revealed by multidimensional integrated analyses - Xingwang Zhao; Mengjie Zhang; Yuying Jia; Wenying Liu; Shifei Li; Cuie Gao; Lian Zhang; Bing Ni; Zhihua Ruan; Rui Dong (Inflammation Research, 2023)

Genetic algorithm-based parameter inversion and pipeline subsidence prediction - Lian Xue; Xue Zhao; Hu Li; Jie Zheng; Xiuqiang Lei; Xue Gong (Journal of Applied Geophysics, 2023)

Heat waves accelerate the spread of infectious diseases - Xinbo Lian; Jianping Huang; Han Li; Yongli He; Zhi Ouyang; Songbo Fu; Yingjie Zhao; Danfeng Wang; Rui Wang; Xiaodan Guan (Environmental Research, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Effect of the Flagellar Gene fliL on the Virulence of Pseudomonas plecoglossicida to Hybrid Grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Lian Shi; Junjie Zhang; Lingmin Zhao; Qi Li; Lixing Huang; Yingxue Qin; Qingpi Yan (Fishes, 2023)
Pseudomonas plecoglossicida is the pathogen of visceral white spot disease in marine fish, which usually occurs at 16–19 °C and has resulted in heavy economic losses. Our previous RNA sequencing revealed that the expression of the fliL gene in P. plecoglossicida was significantly up-regulated during infection of the host. In order to study the influence of the fliL gene on the virulence of P. plecoglossicida, the fliL gene of the NZBD9 strain was knocked out by the homologous recombination method, the fliL gene-deleted strain (ΔfliL strain) constructed, and complemented the fliL gene to the ΔfliL strain to obtain the C-ΔfliL strain. The growth curves of the NZBD9 strain, ΔfliL strain, and C-ΔfliL strain did not show significant differences. Compared with the NZBD9 strain, the motility, adhesion, and biofilm formation ability were tendered in the ΔfliL strain (p

Study on penetration resistance for thin-walled bucket foundation in muddy clay - Jijian Lian; Xinyi Li; Zhaolin Jia; Hao Zhao; Nan Shao; Zhichuan Wu; Shuaiqi He; Han Wu; Xiaoxu Zhang (Ocean Engineering, 2023)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Abundant tannic acid modified gelatin/sodium alginate biocomposite hydrogels with high toughness, antifreezing, antioxidant and antibacterial properties - Xiumei Zhang; Kejun Liu; Miao Qin; Weiwei Lan; Longfei Wang; Ziwei Liang; Xiaochun Li; Yan Wei; Yinchun Hu; Liqin Zhao; Xiaojie Lian; Di Huang (Carbohydrate Polymers, 2023)

Experimental and numerical research on the wet-towing of wide-shallow bucket jacket foundation for offshore substation - Haijun Wang; Chang Liu; Yaohua Guo; Yue Zhao; Xinyu Li; Jijian Lian (Ocean Engineering, 2023)

Effective purification of the low-rank coal by the collaboration of the microemulsion collector and the CO2 nanobubbles - Fan Lian; Lijun Deng; Guosheng Li; Yijun Cao; Baoxun Zhao; Kai Fan (Fuel, 2023)

Combined effects of SSII-2RNAi and different Wx alleles on rice grain transparency and physicochemical properties - Yan Lu; Dongjing Lv; Lian Zhou; Yong Yang; Weizhuo Hao; Lichun Huang; Xiaolei Fan; Dongsheng Zhao; Qianfeng Li; Changquan Zhang; Qiaoquan Liu (Carbohydrate Polymers, 2023)

A review of the influence of courtyard geometry and orientation on microclimate - Jiayin Zhu; Juanjuan Feng; Jifu Lu; Yu Chen; Weilin Li; Peiji Lian; Xi Zhao (Building and Environment, 2023)

Preparation of mixed matrix membranes by layered double hydroxides of amino acid intercalation and Pebax for ameliorated CO2 separation - Hui Guo; Shaohan Lian; Run Li; Yijuan Zhang; Quan Zhao; Chunfeng Song (Journal of Environmental Chemical Engineering, 2023)

How do people set air conditioning temperature setpoint in urban domestic–Behavior model in Chinese three climate zones based on historical usage data - Junmeng Lyu; Jinbo Li; Zisheng Zhao; Xiongwei Miao; Heng Du; Dayi Lai; Yuxin Yang; Zhiwei Lian (Energy and Buildings, 2023)

Molten salt synthesis of submicron NiNb2O6 anode material with ultra-high rate performance for lithium-ion batteries - Shuo Zhao; Jiabiao Lian; Shan Zhang; Yingxue Cui; Guochun Li; Yong Wang; Huaming Li (Chemical Engineering Journal, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Preliminary Investigation on Marine Radar Oil Spill Monitoring Method Using YOLO Model - Bo Li; Jin Xu; Xinxiang Pan; Rong Chen; Long Ma; Jianchuan Yin; Zhiqiang Liao; Lilin Chu; Zhiqiang Zhao; Jingjing Lian; Haixia Wang (Journal of Marine Science and Engineering, 2023)
Due to the recent rapid growth of ocean oil development and transportation, the offshore oil spill risk accident probability has increased unevenly. The marine oil spill poses a great threat to the development of coastal cities. Therefore, effective and reliable technologies must be used to monitor oil spills to minimize disaster losses. Based on YOLO deep learning network, an automatic oil spill detection method was proposed. The experimental data preprocessing operations include noise reduction, gray adjustment, and local contrast enhancement. Then, real and synthetically generated marine radar oil spill images were used to make slice samples for training the model in the YOLOv5 network. The detection model can identify the effective oil spill monitoring region. Finally, an adaptive threshold was applied to extract the oil slicks in the effective oil spill monitoring regions. The YOLOv5 detection model generated had the advantage of high efficiency compared with existing methods. The offshore oil spill detection method proposed can support real-time and effective data for routine patrol inspection and accident emergency response.

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Responses of carbon and water use efficiencies to climate and land use changes in China's karst areas - Biqin Xiao; Xiaoyong Bai; Cuiwei Zhao; Qiu Tan; Yangbing Li; Guangjie Luo; Luhua Wu; Fei Chen; Chaojun Li; Chen Ran; Xuling Luo; Huipeng Xi; et al. (Journal of Hydrology, 2023)

Stem Cell-derived Extracellular Vesicles: A Promising Nano Delivery Platform to the Brain? - Yuying Guo; Dongsheng Hu; Lu Lian; Linna Zhao; Mingli Li; Huijing Bao; Shixin Xu (Stem Cell Reviews and Reports, 2023)

Seismic Multiple Attenuation in the Continent–Ocean Transition Zone of the Northern South China Sea - Nan Chen; Chun-Feng Li; Yong-Lin Wen; Peng Wang; Xiu-Lian Zhao; Xiao-Li Wan (Journal of Marine Science and Engineering, 2023)
In this study, we process four new multichannel reflection seismic profiles acquired in 2015 and 2016 in the continent–ocean transition zone (COT) of the northern South China Sea (SCS). We apply a multi-domain, progressive, and seabed-controlled denoising technique and obtain a good denoising effect. Combining velocity analysis in the multi-round time domain and forward modeling, we analyze the types and characteristics of multiples in the study area and formulate an effective demultiple technique to attenuate strong seabed multiples, diffracted multiples from rough seafloor, and other multiples from deep reflectors. The processing results show that the sea surface-related multiple elimination technique predicts the sea surface-related multiples accurately by data convolution, and has a good effect in attenuating seabed multiples. Diffracted multiple attenuation method extracts high-frequency and high-energy diffracted multiples, and suppresses multiples by the energy ratios of multiples to primary events. To attenuate deep multiples, we select predictive deconvolution to attenuate periodic deep multiples after many trials and detailed analysis. The combination of these different techniques in sequence proves to be quite effective in attenuating different seismic multiples in the COT. The imaged crustal structures near the COT often show strong magmatism and/or basement uplifting. The faulted and thinned continental crust adjacent to the COT corresponds to the lowest free-air gravity anomalies. Gravity anomalies often increase from the COT to the oceanic crust. An exception is to the northeast of the SCS, where the relatively wide COT shows very high gravity anomalies, likely induced by mantle upwelling and serpentinization.

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Template-induced mesoporous Ni–Al oxide catalysts with tuned physico–chemical properties for the oxidative dehydrogenation of ethane - Lian Kong; Dong Li; Jingying Bi; Xiaoqiang Fan; Zean Xie; Xia Xiao; Zhen Zhao (Chemical Engineering Journal, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

A NIR Fluorescent Probe Benzopyrylium Perchlorate-based for Visual Sensing and Imaging of SO2 Derivatives in Living Cells - Xiao Ye Luo; Juan Xie; Guang Lian Zhao; Gui Yong Li; Hang Da Qu; Yu Zhu Yang (Journal of Fluorescence, 2023)

Dissection of mendelian predisposition and complex genetic architecture of craniovertebral junction malformation - Zhenlei Liu; Huakang Du; Hengqiang Zhao; Siyi Cai; Sen Zhao; Yuchen Niu; Xiaoxin Li; Bowen Liu; Yingzhao Huang; Jiashen Shao; Lian Liu; Ye Tian; et al. (Human Genetics, 2023)

Development and Testing of a High-Resolution Three-Dimensional Seismic Detection System for Gas Hydrate - Chenguang Liu; Qingxian Zhao; Zhen Liu; Yanhong Lian; Yanliang Pei; Baohua Liu; Xishuang Li; Qingjie Zhou; Keping Yan; Zili Chen (Journal of Marine Science and Engineering, 2022)
As a novel type of mineral resource, gas hydrate has received a considerable amount of attention worldwide. This seismic detection method can detect abnormal phenomena such as the BSR, blank zones, velocity anomalies and polarity inversion of gas hydrate and become an important method of gas hydrate detection. The occurrence area of gas hydrate in the South China Sea is usually buried deep beneath the seabed. The current method cannot meet the needs of the shape and structure detection of gas hydrate deposits. With the support of the National Key R&D Program of China, some key technologies have led to developmental breakthroughs, such as ultra-high-energy plasma sources, small-group-interval high-resolution seismic streamers, and distributed three-dimensional seismic acquisition. The seismic profile obtained north of the South China Sea shows that the stratum penetration depth reaches nearly 1000 m at a depth of 1500 m, and the vertical resolution is better than 1.5 m. This system can serve the needs of high-resolution exploration of gas hydrate resources.

Protective effects of isofraxidin against scopolamine-induced cognitive and memory impairments in mice involve modulation of the BDNF-CREB-ERK signaling pathway - Bingliang Lian; Jingwen Gu; Chen Zhang; Zhicong Zou; Meng Yu; Fanghong Li; Xiaoli Wu; Allan Zijian Zhao (Metabolic Brain Disease, 2022)

Double knock-in pig models with elements of binary Tet-On and phiC31 integrase systems for controllable and switchable gene expression - Qin Jin; Xiaoyu Yang; Shixue Gou; Xiaoyi Liu; Zhenpeng Zhuang; Yanhui Liang; Hui Shi; Jiayuan Huang; Han Wu; Yu Zhao; Zhen Ouyang; Quanjun Zhang; et al. (Science China Life Sciences, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Gastrodin Attenuates Lipopolysaccharide-Induced Inflammatory Response and Migration via the Notch-1 Signaling Pathway in Activated Microglia - Yue-yi Yao; Run Li; Yan-ji Guo; Yu Zhao; Jia-zhi Guo; Qing-long Ai; Lian-mei Zhong; Di Lu (NeuroMolecular Medicine, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Analysis of expression profiles and bioinformatics suggests that plasma exosomal circular RNAs may be involved in ischemic stroke in the Chinese Han population - Bingyi Xu; Xianli Huang; Yan Yan; Zhi Zhao; Jialei Yang; Lulu Zhu; Yibing Yang; Baoyun Liang; Lian Gu; Li Su (Metabolic Brain Disease, 2022)

Influence of the rs6736 Polymorphism on Ischemic Stroke Susceptibility in Han Chinese Individuals via the Disruption of miR-7–1 Binding to the C14orf119 Gene - Xiaojing Guo; Lulu Zhu; Xinyi Zhao; Xulong Wu; Jialei Yang; Jiao Huang; Lian Gu; Li Su (Journal of Molecular Neuroscience, 2022)

Exosomal miRNA-328-3p targets ZO-3 and inhibits porcine epidemic diarrhea virus proliferation - Han Zhao; Jinxin Yang; Qian Wang; Zhanding Cui; Dengliang Li; Jiangting Niu; Yanbing Guo; Qian Zhang; Shuang Zhang; Yanli Zhao; Kai Wang; Wei Lian; et al. (Archives of Virology, 2022)

Stability analysis of slopes reinforced with anchor cables and optimal design of anchor cable parameters - Dong-Ping Deng; Liang Li; Lian-Heng Zhao (European Journal of Environmental and Civil Engineering, 2021)

PPM1F in Dentate Gyrus Modulates Anxiety-Related Behaviors by Regulating BDNF Expression via AKT/JNK/p-H3S10 Pathway - Fantao Meng; Jing Liu; Juanjuan Dai; Haifeng Lian; Shujun Jiang; Qiongyu Li; Min Wu; Wentao Wang; Dan Wang; Di Zhao; Cuilan Liu; Changyun Qiu; et al. (Molecular Neurobiology, 2021)

Gga-miR-181a modulates ANP32A expression and inhibits MDCC-MSB-1 cell - X. Li; C. Zhao; B. Han; L. Qu; C. Liu; N. Yang; L. Lian (In Vitro Cellular & Developmental Biology - Animal, 2021)

Investigation on petrophysical properties of fractured tight gas sandstones: a case study of Jurassic Xujiahe Formation in Sichuan Basin, Southwest China - Huawei Zhao; Xiaofei Shang; Meng Li; Wenbiao Zhang; Shuang Wu; Peiqing Lian; Taizhong Duan (Arabian Journal of Geosciences, 2021)

MicroRNA-203a regulates pancreatic β cell proliferation and apoptosis by targeting IRS2 - Xianlan Duan; Lian Zhao; Wancun Jin; Qinxin Xiao; Yani Peng; Gan Huang; Xia Li; Sonia DaSilva-Arnold; Haibo Yu; Zhiguang Zhou (Molecular Biology Reports, 2020)

The core regulatory networks and hub genes regulating flower development in Chrysanthemum morifolium - Lian Ding; Aiping Song; Xue Zhang; Song Li; Jiangshuo Su; Weikang Xia; Kunkun Zhao; Wenqian Zhao; Yunxiao Guan; Weimin Fang; Sumei Chen; Jiafu Jiang; et al. (Plant Molecular Biology, 2020)

Correction to: Transcriptomic Profiling Provides Insights into Inbreeding Depression in Yesso Scallop Patinopecten yessoensis - Liang Zhao; Yangping Li; Jiarun Lou; Zhihui Yang; Huan Liao; Qiang Fu; Zhenyi Guo; Shanshan Lian; Xiaoli Hu; Zhenmin Bao (Marine Biotechnology, 2020)

Transcriptomic Profiling Provides Insights into Inbreeding Depression in Yesso Scallop Patinopecten yessoensis - Liang Zhao; Yangping Li; Jiarun Lou; Zhihui Yang; Huan Liao; Qiang Fu; Zhenyi Guo; Shanshan Lian; Xiaoli Hu; Zhemin Bao (Marine Biotechnology, 2019)

A Fundamental Investigation of the Tensile Failure of Rock Using the Three-Dimensional Lattice Spring Model - Qin Li; Gao-Feng Zhao; Jijian Lian (Rock Mechanics and Rock Engineering, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

Influence of shrub roots on soil macropores using X-ray computed tomography in a shrub-encroached grassland in Northern China - Xia Hu; Xiao-Yan Li; Lan-Lan Guo; Yong Liu; Pei Wang; Yun-Duo Zhao; Ya-Qian Cheng; Yan-Li Lyu; Lian-You Liu (Journal of Soils and Sediments, 2019)

Analysis of miRNA-seq in the liver of common carp (Cyprinus carpio L.) in response to different environmental temperatures - JunLong Sun; LiuLan Zhao; Hao Wu; WenQiang Lian; Can Cui; ZongJun Du; Wei Luo; MingZhou Li; Song Yang (Functional & Integrative Genomics, 2019)

Influence of non-dimensional strength parameters on the seismic stability of cracked slopes - Lian-heng Zhao; Xiao Cheng; De-jian Li; Ying-bin Zhang (Journal of Mountain Science, 2019)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Distinct Element Modelling of a Landslide Triggered by the 5.12 Wenchuan Earthquake: A Case Study - Zhi-Chen Song; Lian-Heng Zhao; Liang Li; Yingbin Zhang; Gaopeng Tang (Geotechnical and Geological Engineering, 2018)

The effects of CXCL10 polymorphisms on COPD susceptibility - Yan Wang; Qipeng Zhou; Lian Dong; Mingmei Xiong; Hua Jiang; Meihua Guo; Li Zhao; Liang Yuan; Ziying Li; Hanwei Liu; Jian Wang; Nanshan Zhong; et al. (Molecular Genetics and Genomics, 2018)

Impact of International Collaborative Training Programs on Medical Students’ Research Ability - Remila Rezhake; Shang-Ying Hu; Yu-Qian Zhao; Li Zhang; Xue-Lian Zhao; Ayling Z. Dominguez; You-Lin Qiao; Cai-Hong Zhou; Fang-Hui Zhao (Journal of Cancer Education, 2018)

Structures and bioactivities of seven flavonoids from Osmanthus fragrans ‘Jinqiu’ essential oil extraction residues - Jiang-Lian Zhou; Xian-Ying Fang; Jing-Qiu Wang; Lin-Guo Zhao; Yi Li; Feng Tang; Yong-De Yue (Natural Product Research, 2018)

A Numerical Study on Toppling Failure of a Jointed Rock Slope by Using the Distinct Lattice Spring Model - Ji-Jian Lian; Qin Li; Xi-Fei Deng; Gao-Feng Zhao; Zu-Yu Chen (Rock Mechanics and Rock Engineering, 2018)

Prognostic Utility of Fatty Acid-Binding Protein 4 in Patients with Type 2 Diabetes and Acute Ischemic Stroke - Siou Li; Pengxiang Bi; Weina Zhao; Yifei Lian; Haifu Zhu; Dan Xu; Jiayuan Ding; Quankui Wang; Changhao Yin (Neurotoxicity Research, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Limit equilibrium method (LEM) of slope stability and calculation of comprehensive factor of safety with double strength-reduction technique - Dong-ping Deng; Liang Li; Lian-heng Zhao (Journal of Mountain Science, 2017)

Geochemistry and tectonic significance of the Gongzhu peridotites in the northern branch of the western Yarlung Zangbo ophiolitic belt, western Tibet - Dongyang Lian; Jingsui Yang; Fei Liu; Weiwei Wu; Li Zhang; Hui Zhao; Jian Huang (Mineralogy and Petrology, 2017)

The complete mitochondrial genome of the monophagous moth Protegira songi (Lepidoptera: Noctuidae) - Guo Xiao-Hui; Cheng Ming-Yang; Hou Ya-Feng; Deng Tuan-Tuan; Zhao Sha; Yu Hai-Li; Xing Lian-Xi (Conservation Genetics Resources, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Inhibitory Effect of Endomorphin-2 Binding to the μ-Opioid Receptor in the Rat Pre-Bötzinger Complex on the Breathing Activity - Jian Qi; Hui Li; Ting-Bao Zhao; Ya-Cheng Lu; Ting Zhang; Jin-Lian Li; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2017)

Overexpression of Tau Rescues Nogo-66-Induced Neurite Outgrowth Inhibition In Vitro - Yu-Chao Zuo; Hong-Lian Li; Nan-Xiang Xiong; Jian-Ying Shen; Yi-Zhi Huang; Peng Fu; Hong-Yang Zhao (Neuroscience Bulletin, 2016)

Effects of salinity on simultaneous reduction of perchlorate and nitrate in a methane-based membrane biofilm reactor - Yin Zhang; Jia-Xian Chen; Li-Lian Wen; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Captopril improves postresuscitation hemodynamics protective against pulmonary embolism by activating the ACE2/Ang-(1-7)/Mas axis - Hong-Li Xiao; Chun-Sheng Li; Lian-Xing Zhao; Jun Yang; Nan Tong; Le An; Qi-Tong Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Reliability back analysis of shear strength parameters of landslide with three-dimensional upper bound limit analysis theory - Lian-Heng Zhao; Shi Zuo; Yu-Liang Lin; Liang Li; Yingbin Zhang (Landslides, 2016)

Chicken gga-miR-130a targets HOXA3 and MDFIC and inhibits Marek’s disease lymphoma cell proliferation and migration - Bo Han; Ling Lian; Xin Li; Chunfang Zhao; Lujiang Qu; Changjun Liu; Jiuzhou Song; Ning Yang (Molecular Biology Reports, 2016)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)

Evolution of the microbial community of the biofilm in a methane-based membrane biofilm reactor reducing multiple electron acceptors - Ran Chen; Yi-Hao Luo; Jia-Xian Chen; Yin Zhang; Li-Lian Wen; Ling-Dong Shi; Youneng Tang; Bruce E. Rittmann; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2016)

Effects of Different Zinc Species on Cellar Zinc Distribution, Cell Cycle, Apoptosis and Viability in MDAMB231 Cells - Yan-hong Wang; Wen-jie Zhao; Wei-juan Zheng; Li Mao; Hong-zhen Lian; Xin Hu; Zi-chun Hua (Biological Trace Element Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Variation of molybdenum isotopes in molybdenite from porphyry and vein Mo deposits in the Gangdese metallogenic belt, Tibetan plateau and its implications - Yong Wang; Lian Zhou; Shan Gao; Jian-Wei Li; Zhi-Fang Hu; Lu Yang; Zhao-Chu Hu (Mineralium Deposita, 2016)

Production of CCL20 on nucleus pulposus cells recruits IL-17-producing cells to degenerated IVD tissues in rat models - Yuanqiang Zhang; Lian Liu; Shuaishuai Wang; Yunpeng Zhao; Yi Liu; Jingkun Li; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2016)

Investigation of the ASR family in foxtail millet and the role of ASR1 in drought/oxidative stress tolerance - Zhi-Juan Feng; Zhao-Shi Xu; Jiutong Sun; Lian-Cheng Li; Ming Chen; Guang-Xiao Yang; Guang-Yuan He; You-Zhi Ma (Plant Cell Reports, 2016)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Mapping toll-like receptor signaling pathway genes of Zhikong scallop (Chlamys farreri) with FISH - Bosong Zhao; Liang Zhao; Huan Liao; Jie Cheng; Shanshan Lian; Xuan Li; Xiaoting Huang; Zhenmin Bao (Journal of Ocean University of China, 2015)

Changes in global DNA methylation intensity and DNMT1 transcription during the aging process of scallop Chlamys farreri - Shanshan Lian; Yan He; Xue Li; Bosong Zhao; Rui Hou; Xiaoli Hu; Lingling Zhang; Zhenmin Bao (Journal of Ocean University of China, 2015)

Chemical constituents from Piper wallichii - Yan-Ni Shi; Lian Yang; Jin-Hua Zhao; Yi-Ming Shi; Yan Qu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Xing-Cong Li; Min Xu; Ying-Jun Zhang (Natural Product Research, 2015)

Effects of the size and morphology of zinc oxide nanoparticles on the germination of Chinese cabbage seeds - Lei Xiang; Hai-Ming Zhao; Yan-Wen Li; Xian-Pei Huang; Xiao-Lian Wu; Teng Zhai; Yue Yuan; Quan-Ying Cai; Ce-Hui Mo (Environmental Science and Pollution Research, 2015)

Apolipoprotein E gene polymorphisms associated with processing speed and executive functions in healthy Han Chinese - Cheng-Cheng Zhang; Hong-Yan Ren; Ming-Li Li; Qiang Wang; Wei Deng; Wan-Jun Guo; Wei Lei; Bo Xiang; Lian-Sheng Zhao; Xiao-Hong Ma; Yong-Gang Yao; Tao Li (Neuroscience Bulletin, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

SIRT1 overexpression in skeletal muscle in vivo induces increased insulin sensitivity and enhanced complex I but not complex II–V functions in individual subsarcolemmal and intermyofibrillar mitochondria - Hao-Hao Zhang; Gui-Jun Qin; Xia-Lian Li; Ying-Hui Zhang; Pei-Jie Du; Peng-Yu Zhang; Yan-Yan Zhao; Jing Wu (Journal of Physiology and Biochemistry, 2015)

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing - Jin-jun Zhang; Meng-meng Cui; Da Fan; De-shan Zhang; Hui-xin Lian; Zhao-yin Yin; Jin Li (Environmental Science and Pollution Research, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Impaired erythrocyte deformability in transgenic HO-1G143H mutant mice - Gan Chen; Yujing Yin; Bo Wang; Penglong Li; Qingjun Liu; Guoxing You; Jingxiang Zhao; Sha Xia; Lian Zhao; Hong Zhou (Transgenic Research, 2015)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

ABI-like transcription factor gene TaABL1 from wheat improves multiple abiotic stress tolerances in transgenic plants - Dong-Bei Xu; Shi-Qing Gao; You-Zhi Ma; Zhao-Shi Xu; Chang-Ping Zhao; Yi-Miao Tang; Xue-Yin Li; Lian-Cheng Li; Yao-Feng Chen; Ming Chen (Functional & Integrative Genomics, 2014)

ClC-3 deficiency protects preadipocytes against apoptosis induced by palmitate in vitro and in type 2 diabetes mice - Yun-Ying Huang; Xiong-Qin Huang; Li-Yan Zhao; Fang-Yun Sun; Wen-Liang Chen; Jie-Yi Du; Feng Yuan; Jie Li; Xue-Lian Huang; Jie Liu; Xiao-Fei Lv; Yong-Yuan Guan; et al. (Apoptosis, 2014)

Numerical experiments on the impact of spring north pacific SSTA on NPO and unusually cool summers in Northeast China - Yi Lian; Bin Zhao; Baizhu Shen; Shangfeng Li; Gang Liu (Advances in Atmospheric Sciences, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

A phylogenetic analysis of the ubiquitin superfamily based on sequence and structural information - Zhen Yang; Haikui Chen; Xiaobo Yang; Xueshuai Wan; Lian He; Ruoyu Miao; Huayu Yang; Yang Zhong; Li Wang; Haitao Zhao (Molecular Biology Reports, 2014)

Effects of hypoxic exercise training on microRNA expression and lipid metabolism in obese rat livers - Ying-li Lu; Wen Jing; Lian-shi Feng; Li Zhang; Jian-fang Xu; Tong-jian You; Jing Zhao (Journal of Zhejiang University-SCIENCE B, 2014)

Establishment of Rat Model of Central Venous Catheter (CVC): Associated Infection and Evaluation of the Virulence of Bacterial Biofilms - Lian-Hua Ye; Yun-Chao Huang; Feng-Li Guo; Xin Liu; Guang-Qiang Zhao; Lin-Can Duan; Cong-Guo Jin (Cell Biochemistry and Biophysics, 2014)

Study the biocatalyzing effect and mechanism of cellulose acetate immobilized redox mediators technology (CE-RM) on nitrite denitrification - Haibo Li; Jianbo Guo; Jing Lian; Zhenhua Xi; Lijun Zhao; Xiaoyu Liu; Chenxiao Zhang; Jingliang Yang (Biodegradation, 2014)

Diverse bacteria isolated from microtherm oil-production water - Ji-Quan Sun; Lian Xu; Zhao Zhang; Yan Li; Yue-Qin Tang; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2014)

Coronary heart disease diagnosis bases on the change of different parts in treadmill exercise test ECG - Sun Jian-ling; Zhao Ying; Gao Yu-lian; Xiong Li-juan; Guo Ji-hong; Li Xiao-ying (Cell Biochemistry and Biophysics, 2013)

Elderly Patients and Coronary Heart Disease on Response to Treadmill Exercise Test - Jian-ling Sun; Guo-lan Gao; Ying Zhao; Yu-lian Gao; Li-juan Xiong; Ji-hong Guo; Xiao-ying Li (Cell Biochemistry and Biophysics, 2013)

A Fluorescent Turn-On Probe Based on Benzo [E] Indolium for Cyanide Ion in Water With High Selectivity - Yue Sun; Shanwei Fan; Dong Zhao; Lian Duan; Ruifeng Li (Journal of Fluorescence, 2013)

Cytochrome P450 oxidoreductase genetic polymorphisms A503V and rs2868177 do not significantly affect warfarin stable dosage in Han-Chinese patients with mechanical heart valve replacement - Sheng-Lan Tan; Zhi Li; Wei Zhang; Guo-Bao Song; Li-Ming Liu; Juan Peng; Zhao-Qian Liu; Lan Fan; Xiang-Guang Meng; Lian-Sheng Wang; Yao Chen; Xin-Min Zhou; et al. (European Journal of Clinical Pharmacology, 2013)

Uptake of arsenic species by turnip ( Brassica rapa L.) and lettuce ( Lactuca sativa L.) treated with roxarsone and its metabolites in chicken manure - Lian Xi Huang; Li Xian Yao; Zhao Huan He; Chang Min Zhou; Guo Liang Li; Bao Mei Yang; Ying Fen Li (Food Additives & Contaminants: Part A, 2013)

Climate change trend in China, with improved accuracy - Tian-Xiang Yue; Na Zhao; R. Douglas Ramsey; Chen-Liang Wang; Ze-Meng Fan; Chuan-Fa Chen; Yi-Min Lu; Bai-Lian Li (Climatic Change, 2013)

Effects of Exogenous Zinc on Cell Cycle, Apoptosis and Viability of MDAMB231, HepG2 and 293 T Cells - Yan-hong Wang; Ke-jin Li; Li Mao; Xin Hu; Wen-jie Zhao; An Hu; Hong-zhen Lian; Wei-juan Zheng (Biological Trace Element Research, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Marker-assisted selection of Verticillium wilt resistance in progeny populations of upland cotton derived from mass selection-mass crossing - Cheng-Qi Li; Guan-Shen Liu; Hai-Hong Zhao; Li-Juan Wang; Xiao-Fei Zhang; Ying Liu; Wan-Yang Zhou; Liu-Liu Yang; Peng-Bo Li; Qing-Lian Wang (Euphytica, 2013)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Isolation and identification of a wheat gene encoding a zinc finger protein (TaZnFP) responsive to abiotic stresses - Dong-Hong Min; Yue Zhao; Dong-Ying Huo; Lian-Cheng Li; Ming Chen; Zhao-Shi Xu; You-Zhi Ma (Acta Physiologiae Plantarum, 2013)

Flow Karyotyping of Wheat Addition Line “T240” with a Haynaldia villosa 6VS Telosome - Dong-wei Guo; Dong-hong Min; Zhao-shi Xu; Ming Chen; Lian-cheng Li; Muhammad Ashraf; Abdul Ghafoor; You-zhi Ma (Plant Molecular Biology Reporter, 2013)

Genetic diversity in Artemisia halodendron (Asteraceae) based on chloroplast DNA psbA–trnH region from different hydrothermal conditions in Horqin sandy land, northern China - Wenda Huang; Xueyong Zhao; Xin Zhao; Yuqiang Li; Xiaoan Zuo; Jie Lian; Yongqing Luo (Plant Systematics and Evolution, 2013)

Impacts of polar vortex, NPO, and SST configurations on unusually cool summers in Northeast China. Part I: Analysis and diagnosis - Yi Lian; Baizhu Shen; Shangfeng Li; Bin Zhao; Zongting Gao; Gang Liu; Ping Liu; Ling Cao (Advances in Atmospheric Sciences, 2013)

Induction Kinetics of a Novel Stress-related LEA Gene in Wheat - Dong-Hong Min; Xiao-Hong Zhang; Zhao-Shi Xu; Yue Zhao; Yang Chen; Lian-Cheng Li; Ming Chen; You-Zhi Ma (Plant Molecular Biology Reporter, 2012)

The role and clinical implications of microRNAs in hepatocellular carcinoma - Xue Zhao; Zhen Yang; GuangBing Li; DongKai Li; Yi Zhao; Yan Wu; Simon C. Robson; Lian He; YiYao Xu; RuoYu Miao; HaiTao Zhao (Science China Life Sciences, 2012)
Hepatocellular carcinoma (HCC) is common and one of the most aggressive of all human cancers. Recent studies have indicated that miRNAs, a class of small noncoding RNAs that regulate gene expression post-transcriptionally, directly contribute to HCC by targeting many critical regulatory genes. Several miRNAs are involved in hepatitis B or hepatitis C virus replication and virus-induced changes, whereas others participate in multiple intracellular signaling pathways that modulate apoptosis, cell cycle checkpoints, and growth-factor-stimulated responses. When disturbed, these pathways appear to result in malignant transformation and ultimately HCC development. Recently, miRNAs circulating in the blood have acted as possible early diagnostic markers for HCC. These miRNA also could serve as indicators with respect to drug efficacy and be prognostic in HCC patients. Such biomarkers would assist stratification of HCC patients and help direct personalized therapy. Here, we summarize recent advances regarding the role of miRNAs in HCC development and progression. Our expectation is that these and ongoing studies will contribute to the understanding of the multiple roles of these small noncoding RNAs in liver tumorigenesis.

Mechanistic insights into the link between visfatin gene C-1535T polymorphism and coronary artery disease: an in vitro study - Yong-Sheng Wang; Wei Gao; Hong-Fen Li; Ze-Mu Wang; Jun Zhu; Huan Zhao; Jian-Jun Yan; En-Zhi Jia; Zhi-Jian Yang; Lian-Sheng Wang (Molecular and Cellular Biochemistry, 2012)

Two new xanthones from the pericarp of Garcinia mangostana - Yan Zhao; Jin-Ping Liu; Dan Lu; Ping-Ya Li; Lian-Xue Zhang (Natural Product Research, 2012)

In Vitro Model of Bacterial Biofilm Formation on Polyvinyl Chloride Biomaterial - Guang-qiang Zhao; Lian-hua Ye; Yun-chao Huang; Da-kuan Yang; Li Li; Geng Xu; Yu-jie Lei (Cell Biochemistry and Biophysics, 2011)

QSAR study for cytotoxicity of diterpenoid tanshinones - Mei-Lian Zhao; Jia-Jian Yin; Meng-Long Li; Ying Xue; Yong Guo (Interdisciplinary Sciences: Computational Life Sciences, 2011)

A new antioxidant xanthone from the pericarp of Garcinia mangostana Linn. - Yan Zhao; Jin-Ping Liu; Dan Lu; Ping-Ya Li; Lian-Xue Zhang (Natural Product Research, 2010)

Isolation and characterization of a gene encoding a polyethylene glycol-induced cysteine protease in common wheat - Qing-Wei Zang; Cai-Xiang Wang; Xu-Yan Li; Zhi-Ai Guo; Rui-Lian Jing; Jun Zhao; Xiao-Ping Chang (Journal of Biosciences, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Isolation and Characteristics of the CN Gene, a Tobacco Mosaic Virus Resistance N Gene Homolog, from Tobacco - Gai-Yun Zhang; Ming Chen; Jia-Ming Guo; Tong-Wen Xu; Lian-Cheng Li; Zhao-Shi Xu; You-Zhi Ma; Xue-Ping Chen (Biochemical Genetics, 2009)

Overexpression of Thellungiella halophila H+-PPase (TsVP) in cotton enhances drought stress resistance of plants - Su-Lian Lv; Li-Jun Lian; Pei-Lin Tao; Zhao-Xia Li; Ke-Wei Zhang; Ju-Ren Zhang (Planta, 2009)

A cotton (Gossypium hirsutum) DRE-binding transcription factor gene, GhDREB, confers enhanced tolerance to drought, high salt, and freezing stresses in transgenic wheat - Shi-Qing Gao; Ming Chen; Lian-Qin Xia; Hui-Jun Xiu; Zhao-Shi Xu; Lian-Cheng Li; Chang-Ping Zhao; Xian-Guo Cheng; You-Zhi Ma (Plant Cell Reports, 2009)

Isolation and functional characterization of HvDREB1—a gene encoding a dehydration-responsive element binding protein in Hordeum vulgare - Zhao-Shi Xu; Zhi-Yong Ni; Zhi-Yong Li; Lian-Cheng Li; Ming Chen; Dong-Yao Gao; Xiu-Dao Yu; Pei Liu; You-Zhi Ma (Journal of Plant Research, 2009)

Characterization of the TaAIDFa gene encoding a CRT/DRE-binding factor responsive to drought, high-salt, and cold stress in wheat - Zhao-Shi Xu; Zhi-Yong Ni; Li Liu; Li-Na Nie; Lian-Cheng Li; Ming Chen; You-Zhi Ma (Molecular Genetics and Genomics, 2008)

Involvement of ERK and AKT signaling in the growth effect of arginine vasopressin on adult rat cardiac fibroblast and the modulation by simvastatin - Yan-Ping He; Lian-You Zhao; Qiang-Sun Zheng; Shao-Wei Liu; Xiao-Yan Zhao; Xiao-Long Lu; Xiao-Lin Niu; Xia Li (Molecular and Cellular Biochemistry, 2008)

Effects of RNA interference-induced tryptase down-regulation in P815 cells on IL-6 and TNF-α release of endothelial cells - Yi-feng Jiang; Feng-di Zhao; Xiao-bo Li; Yan-xia Ning; Xiu-ling Zhi; Rui-zhe Qian; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Climatic features of summer temperature in northeast china under warming background - Ji Li; Qiang Gong; Lian-wei Zhao (Chinese Geographical Science, 2005)

Expression of insulin-like growth factor (IGF)-II in human prostate, breast, bladder, and paraganglioma tumors - Shu-Lian Li; Hideki Goko; Zhao-Dong Xu; G. Kimura; Yanyu Sun; Mark H. Kawachi; Timothy G. Wilson; Sharon Wilczynski; Y. Fujita-Yamaguchi (Cell and Tissue Research, 1998)